Conceptualization of Soft Skills as Part of the Professional Socialization of Social Workers - Shaffie, Fuziah (UUM Press, 2016)
This article discusses the conceptualization of soft skills which current higher institutions educators of professional programmes should contemplate. Social work educators were probed to describe their experiences within their profession, and viewpoints on, soft skills as part of the professional socialization of social workers toward becoming professionally and socially competent when providing their services to their clients. In-depth interviews were used as means of gathering qualitative data. The transcribed data was then thematically analyzed. This paper highlights the opinions of two social work educators, from two public universities, on the issue of soft skills among social workers. The social work educators insinuated that it is important to raise awareness of soft skills competencies among social work educators to help them in assessing themselves, and identify where and how they could actively seek to improve themselves as trainers or teachers of social workers to function effectively within the context of their workplaces. Embedding the soft skills competencies into their career as social workers is assumed as one of the effective and efficient method of achieving both professional and social competence. The proposed soft skills provided early ideas and initiatives which can serve as guideline when facilitating and guiding future qualified social workers.